Impact of digital interdisciplinary consultation on secondary care referrals by general practitioners: a protocol for a stepped-wedge cluster randomised controlled trial - Maarten Postma; Danielle Jansen; Henk van der Worp; Marco H Blanker; Henk Schers; Sanne Sanavro; Joke Stoffelen; Paul Koning; Michiel de Boer; Guus Janus (BMJ Open)
Introduction Optimal collaboration between general practice and hospital care is crucial to maintain affordable and sustainable access to healthcare for the entire population. General practitioners (GPs) are the gatekeepers to specialist care and patients will visit hospitals mostly only after referral. However, a substantial part of these referrals may be inappropriate, as communication between GPs and medical specialists can be challenging and referring patients may be the most obvious action for a GP to perform.A new digital platform (Prisma) connects GPs and specialists in interdisciplinary groups and facilitates asynchronous, accessible and fast teleconsultation within the group. No previous research has been done to evaluate the impact of this new platform on the referral rates to the hospital.Methods and analysis A stepped-wedge randomised controlled trial (RCT) will be performed in Zwolle region in the Netherlands to analyse the effect of introduction of the platform on rate of inappropriate referrals to orthopaedic surgery. In four steps, GPs in the region will be given access to the platform. GPs will be part of the control condition until randomisation to the intervention. According to our sample size calculation, we need to include 18 practices with 1008 patients presenting with hip and knee symptoms. Routine care data of hospital registrations will be analysed to calculate the rate of inappropriate referrals (primary outcome). Secondary outcome are costs, primary and secondary care workload, posted cases and user satisfaction. Alongside this quantitative analysis, we will evaluate patient experience, facilitators and barriers for use of the platform.Ethics and dissemination The medical ethics review board of University Medical Center Groningen (UMCG), the Netherlands (METc-number: 2021/288) has confirmed that the Medical Research Involving Human Subjects Act (WMO) does not apply to the process evaluation because the study does not involve randomisation of patients or different medical treatments (letter number: M21.275351).Trial registration number NL9704.